Medical control program of occupational health in brazilian electrical Companies - Lima, Marta Maria Rodrigues; Dantas, Rosane Arruda; Pagliuca, Lorita Marlena Freitag; Almeida, Paulo César de (Rev Rene, 2007)
This is a descriptive study which was accomplished with the objective of learning about the Medical Control Program of Occupational Health at electric power distribution companies aiming to evaluate the data of non-conformities related with risk for the workers and to suggest forms of improving such programs. A questionnaire was answered by seven companies, which reflects all of the Brazilian areas, throughout electronic ways. The analysis and interpretation were divided in three categories: context, development and final report. In a general way, all the energetic companies presented non-conformities; company A presented one item of non-conformity, B presented three items, C four items, D and E six items, F eight, and finally company G presented fourteen nonconformity items. It is concluded that the technical quality of the preventive programs in basic subjects of the worker’s health is doubtful for some companies, what may lead to possible diseases, accidents or deaths at work.